2020
DOI: 10.4085/130-20
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate Student-Athletes' Perceptions of Patient-Centered Care Delivered by Athletic Trainers

Abstract: Context: The core competencies of health care indicate that all medical professionals should provide patient-centered care (PCC), or care that is respectful and responsive to one's values and preferences, during each encounter. Objective: To identify collegiate student-athletes' definition of PCC and measure their perceived level of PCC from an athletic trainer (AT). Design: Cross-sectional study. Setting: Mixed-method survey. Patients or Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Although confidence in one’s ability to implement PCC is important, it is different from successfully performing PCC in a real clinical setting, which has been identified in athletic training as a weakness in emergency care skills and healthcare administration. Athletic training literature has recently started to address the need to measure providers’ application of PCC throughout their care by asking the very patients Ats interact with daily [ 27 ]. When surveyed on how well Ats embody PCC, student-athletes demonstrated strong agreement with the statement that Ats at their college/university delivered care that was respectful of their preferences [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although confidence in one’s ability to implement PCC is important, it is different from successfully performing PCC in a real clinical setting, which has been identified in athletic training as a weakness in emergency care skills and healthcare administration. Athletic training literature has recently started to address the need to measure providers’ application of PCC throughout their care by asking the very patients Ats interact with daily [ 27 ]. When surveyed on how well Ats embody PCC, student-athletes demonstrated strong agreement with the statement that Ats at their college/university delivered care that was respectful of their preferences [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Athletic training literature has recently started to address the need to measure providers’ application of PCC throughout their care by asking the very patients Ats interact with daily [ 27 ]. When surveyed on how well Ats embody PCC, student-athletes demonstrated strong agreement with the statement that Ats at their college/university delivered care that was respectful of their preferences [ 27 ]. These patient findings are significant and match the viewpoints that Ats in our study had for themselves regarding PCC, but more research needs to be done comparing perceptions across all athletic training clinical settings and patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletic training literature has recently started to address the need to measure providers' application of PCC throughout their care by asking the very patients ATs interact with daily. 21 When surveyed on how well ATs embody PCC, student-athletes demonstrated strong agreement with the statement that ATs at their college/university delivered care that was respectful of their preferences. 21 These patient ndings are signi cant and match the viewpoints that ATs in our study had for themselves regarding PCC, but more research needs to be done comparing perceptions across all athletic training clinical settings and patient populations.…”
Section: Dignity and Respectmentioning
confidence: 91%
“…Researchers identified that NCAA Division 1 athletes viewed their ATs as patient-centered providers in the realm of individualized, empathetic care. 37 Athletes have defined empathy through actions of their ATs including patient advocacy, reflective listening, and creating personal connection. 38 The participants in our study felt similarly as in previous research where they were able to develop an empathetic approach to the patient encounter.…”
Section: Patient Approachmentioning
confidence: 99%